ULTRAFILTRATION AS PRETREATMENT OF REVERSE OSMOSIS: LOW FOULING ULTRAFILTRATION MEMBRANE PREPARED FROM POLYETHERSULFONE–AMPHIPHILIC BLOCK COPOLYMER BLEND - Heru Susanto; Luqman Buchori; Siswo Sumardiono; Berkah Fajar; Titik Istirokhatun; I Nyoman Widiasa (Dept. of Chemical Engineering, Diponegoro University, 2009)
This paper demonstrates the preparation of polyethersulfone (PES) ultrafiltration (UF) membranes via wet phase inversion method using either poly(ethylene oxide)-b-poly(propylene oxide)-b- poly(ethylene oxide) (Pluronic®, Plu) or polyethylene glycol (PEG) as hydrophilic modifier. Their effects on membrane structure as well as the resulting membrane performance and their stability in membrane polymer matrix were systematically investigated. The investigated membrane characteristics include surface hydrophilicity (by contact angle), surface chemistry (by FTIR spectroscopy) and water flux measurement. Visualization of membrane surface and cross section morphology was also done by scanning electron microscopy. The membrane performance was examined by investigation of adsorptive fouling and ultrafiltration using solution of bovine serum albumin as the model system. The stability of additive was examined by incubating the membrane in water (40oC) for up to 10 days. The results show that modification effects on membrane characteristic and low fouling behavior were clearly observed. Further, amphiphilic Pluronic generally showed better performance than PEG.